34t=-9

Multiply both sides of the equation by 43.

43⋅34⋅t=43⋅-9

Simplify 43⋅34⋅t.

Cancel the common factor of 4.

Cancel the common factor.

43⋅34⋅t=43⋅-9

Rewrite the expression.

13⋅3⋅t=43⋅-9

13⋅3⋅t=43⋅-9

Cancel the common factor of 3.

Cancel the common factor.

13⋅3⋅t=43⋅-9

Rewrite the expression.

1⋅t=43⋅-9

1⋅t=43⋅-9

Multiply t by 1.

t=43⋅-9

t=43⋅-9

Simplify 43⋅-9.

Cancel the common factor of 3.

Factor 3 out of -9.

t=43⋅(3(-3))

Cancel the common factor.

t=43⋅(3⋅-3)

Rewrite the expression.

t=4⋅-3

t=4⋅-3

Multiply 4 by -3.

t=-12

t=-12

t=-12

Solve for t 3/4t=-9